A GIS-based evaluation of the potential of woody short rotation coppice (SRC) in Portugal aiming at co-firing and decentralized co-generation. (June 2020) - Rodrigues, Abel; Gonçalves, Alexandre B.; Casquilho, Miguel; Gomes, Alberto Azevedo
Abstract: The implementation of woody short rotation coppice in Portugal has a high potential, due to abundant solar radiation and to an availability of about 2.8 Mha of uncultivated derelict marginal areas. In this work, a GIS-based proposal is made to evaluate such potential, considering spatial data for soil use, soil type, site micrometeorology and slope. The proposed species are poplar and eucalypt clones, chosen due to the large implementation of poplar in Europe and to the high biomass productive potential of eucalypt. The latter species was installed for decades in the country, under an intensive coppice management aiming at pulp production. Four main uses for produced biomass are proposed following a mass and energy balances approach, namely: co-firing of 10% biomass in two coal units, combined heat and power cogeneration units with nominal power of 5 MW with organic Rankine cycle technology (CRP-ORC), and smaller pellet units running during 2880 hy -1 . Two scenarios were considered for bioenergy application in each of twelve circular areas of 30 km radius corresponding to low biomass transportation costs: (i) assumption of only new uses and (ii) supplying the major existent conversion units and creating new ones. The estimated area for these SRC cultivations was of around 148.7 kha, with 87.8 kha for eucalypt and 60.9 kha for poplar, delivering a total biomass of about 2.26 Mt, corresponding to a bioenergy of circa 11.7 TWh. Long term effects of a project like this would also contribute for boosting social and economic dynamics of rural communities. Highlights: Woody SRC cultivations are an option for clustered bioenergy production. GIS analysis is very useful for planning of bioenergy production and allocation. CHP(ORC) is a pivotal technology for renewable heat and electricity production. Sustainable co-firing and co-generation are possible with SRC cultivations biomass. Decentralized energy supply boost local economies in rural areas.